Gastrointestinal Distress, State and Trait Anxiety, and Dietary Intake Among College Students During the COVID-19 Pandemic. (7th June 2021) - Evenson, Alexa; Johnson, Katherine; Bohn-Gettler, Catherine; Keyler, Trevor
Abstract: Objectives: To determine the impact of State and Trait anxiety and dietary intake on college students' gastrointestinal symptoms during the COVID-19 pandemic. Methods: A total of 455 students, aged 18–23, from two residential colleges in the midwestern United States participated in the study during April 2021. An online questionnaire that included the National Cancer Institute Dietary Screener, State-Trait Inventory for Cognitive and Somatic Anxiety, and an adapted version of the Gastrointestinal Symptoms Questionnaire was used. Stepwise multiple regression analyses was used to analyze the data. Results: The mean score for GI symptoms was 5.57 ± 5.25. Moderate to severe symptoms of abdominal bloating (31.8%), nausea (16.2%), passing gas (29.1%), abdominal rumbling (28.1%), abdominal cramping (20.4%), diarrhea (18.8%), and constipation (14.7%) were reported by our participants. High rates of State-somatic, State-cognitive, and Trait-somatic anxiety were present in our study population. These anxiety subscales and dietary intake predicted 26% and 3.8% of the GI symptoms variance, respectively. Conclusions: State-anxiety and Trait-somatic anxiety are large factors in predicting GI symptoms compared to dietary intake. College students could seek anxiety-reducing techniques to ease GI symptoms. Funding Sources: None